Sports Field Booking Information System Based on Web: Analysis and Design Approach - Ferry Ardiansyah; Muhamad Yasir Noval; Fauzy Faadillah; Ricky Gunaldo; Wina Witanti (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The process of booking sports fields that still relies on manual methods often causes various obstacles, such as administrative inefficiencies, a high potential for recording and scheduling errors, and limited access to information for users. The gap between the expectation of a fast, accurate, and transparent ordering system and the reality of existing manual systems drives the need for innovative solutions. This research aims to design a web-based sports field booking information system through a systematic system analysis and design approach, as a direct response to these problems. The methodology used is a comprehensive literature study, including the identification of user and manager needs, the collection of scientific references, in-depth analysis of previous research, and the synthesis of findings as the basis for design. This approach ensures that the resulting design is not only innovative but also builds on existing best practices, thereby increasing the relevance and potential for successful implementation. The result of this research is a comprehensive information system design model, including essential features such as user registration and login, search and field selection, a real-time booking process integrated with online payment systems, automatic confirmation, booking history, and data management modules for managers. The design of the system is also supported by detailed design artifacts such as the Use Case Diagram, Sequence Diagram, Deployment Diagram, Entity-Relationship Diagram (ERD), and an intuitive user interface (UI) design.